Underwater Glider Maneuvering Mechanism - Ahmad, Abdul Muhaimin (2017)
Nowadays, underwater vehicles became more popular as the main choice for underwater exploration as it is ideal technologies because of low cost, autonomous and wide range. The development of underwater vehicles needs to be continued to increase the range of operation and also the power consumption which will determine the distance and how long they can operate underwater. Current technologies require high power in terms of maneuvering. Therefore, it is required to further the recent research to enable them to have longer work time so they can cover more area and distance. Aiming at these problems, this paper proposes a new maneuvering system for underwater vehicles. This maneuvering mechanism will reduce the power consumption and depend fully on the buoyancy control to move in the water.